Transobturator male sling TOMS™ for the treatment of stress post-prostatectomy incontinence, initial experience and results with one year's experience - Philippe Grise; Marc Geraud; Jean Lienhart; Benoit Le Portz; Michael Bubenheim; Pierre Costa (International Brazilian Journal of Urology, 2009)
Purpose: Post-prostatectomy incontinence remains a problem, even in minor or moderate degrees. In order to minimize surgical morbidity and costs, sling procedures have been proposed. The authors have developed a new transobturator male sling procedure and report their results after one-year experience. Materials and methods: A prospective multicenter study was conducted in 50 patients with minor or moderate post-prostatectomy incontinence. Evaluation of TOMS™ two arms bulbar sling was based on clinical form assessment, The International Consultation on Incontinence Questionnaire (ICIQ) and short-form (SF) 36 questionnaire pre and postoperatively and at 3, 6, 9 and 12 months. Results: The surgical procedure was considered easy to perform and no post-surgery complication was reported except for one retention. The median number of pads per day decreased significantly from 2 pads before surgery (95% CI: 2 - 3) to 1 during the follow-up period (95% CI: 0 - 2 at 360 days), and at 3 months patients using none or one pad per day were 30% and 32% respectively. The SF 36 continence and quality of life score improved from a median of 100 (95% CI: 83 - 133) to 300 (95% CI: 167 - 375), and the median ICIQ incontinence and quality of life score decreased from 15 (95% CI: 14 - 16) to 8 (95% CI: 5 - 12) one year after surgery. Conclusion: The transobturator perineal male sling TOMS™ is an attractive simple sling technique for moderate or minor post-prostatectomy stress incontinence and offers an improvement in the quality of life.